Theoretical issues of formation of security systems of industrial enterprise development - Мушникова, Світлана Анатоліївна (Technology audit and production reserves, 2015)
Industrial enterprises, the results of which are occupied a leading position in creating the macroeconomic indicators of state national economy, have losses in connection with the change of external and internal situation. Therefore, special attention should be given at present functioning of the main directions of their activity and safety of each direction. During the study of theoretical issues of formation of security systems of industrial enterprise development the main components are determined: the concept of "enterprise development" and "safety of the enterprise activities". It is proved that industrial enterprises that currently are in crisis situations and all their activities that intent to unstable actions should be considered as a socio-ecological-economic system, which requires "shock therapy". In the study it is indicated that effective action for meeting the crisis is the introduction of innovative transformations in each direction of the industrial enterprise ranging from enterprise management system, and ending with environmental activity. It is proved that innovative transformations are happen in conditions of external funding through the involvement of interested investors in the enterprise development. Therefore, the main emphasis of research and the central part of the security of commercial enterprise is proposed a definition of innovative investment component of safety of the enterprise development.